Phrasal verb combinations in corpus-based studies: a critical review - Zarifi, Abdolvahed; Mukundan, Jayakaran (Australian International Academic Centre, 2013)
This study presents a critique of some of the corpus-based studies on phrasal verbs carried out in different types of corpora. Not only is it an attempt to provide the reader with some of the revealing findings these works have to offer but it also tends to critically discuss some of the methodological issues associated with them. It starts off discussing the works done on phrasal verbs in general corpora, then goes on to review the studies dealt with the combinations in learner corpora and ends up with looking into the research focused on the presentation of the phrasal verbs in ELT materials. It is hoped that the methodological issues addressed in the study would be taken into account by the interested researchers in their future research attempts.